Mindfulness And Tourism: The Case Of Penang World Heritage Sites In Malaysia - Tan , Poh Ling; Md Noor, Shuhaida; Mustafa, Hasrina (2015)
It has been propounded that tourists who are mindful are able to value and understand heritage sites better compared to those who are mindless. Mindfulness is a concept that helps tourist build interpretation that will enhance the quality of experience and create a sustainable connection between the tourists and the heritage sites. Mindful tourists are tourists who are actively engaged with the interpretation of the heritage sites resulting in greater learning and understanding. Conversely, a mindless individual is an individual who follows a routine, pay limited attention to what he or she is doing and trapped in a rigid mindset. Past research, however does not indicate an availability of measures of mindfulness in tourism. Thus, this research aims to identify, construct and validate the measure of mindfulness in the context of heritage tourism. This research utilised the quantitative research method and is carried out in Penang, a destination listed under the UNESCO World Heritage Sites. The item questions, to measure mindfulness were developed based on extensive review of past literature. Data were collected through the distribution of questionnaires to 150 local and international tourists. To generate the measure of mindfulness, factor analysis was conducted. Results revealed from the study suggested four distinct factors in measuring mindfulness, namely curiosity and attention, alertness, emotional engagement and openness and flexibility. These key findings derived from the study offer new insights in understanding and quantifying the concept of mindfulness and further improve the model of mindfulness for future application especially in heritage tourism.